2021
DOI: 10.1186/s12938-021-00917-0
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 2 alleviates monosodium iodoacetate-induced oxidative stress, inflammation and apoptosis in chondrocytes via inhibiting aquaporin 4 expression

Abstract: Background Knee osteoarthritis (KOA) is a common cause of disability among the elderly. We aimed to explore the effects of aldehyde dehydrogenase (ALDH) 2 on the progression of KOA and identifying the potential mechanisms. Methods First, ALDH2 expression in knee joint effusion of patients with KOA and the levels of oxidative stress-related markers were determined. After ALDH2 overexpression in monosodium iodoacetate (MIA)-treated SW1353 cells, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In vivo, our study established that Calycosin has anti-apoptotic effects in an MI animal model. These findings corroborated recent findings that reported that Calycosin reduced myocardial apoptosis in a model of cardiac damage induced by doxorubicin (Lu, Lu, Gao, Wang, & Wang, 2021;Zhai et al, 2020) or isoproterenol (Cheng, Zhao, Tse, Le, & Rong, 2015; Huang Khan et al, 2022;Pan et al, 2021), including MI. ALDH2 activation has been shown to enhance anti-oxidative capacity of cells, which is involved in scavenging harmful aldehydes such as MDA and 4-HNE, resulting in a decrease in cellular ROS generation (Islam et al, 2021;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In vivo, our study established that Calycosin has anti-apoptotic effects in an MI animal model. These findings corroborated recent findings that reported that Calycosin reduced myocardial apoptosis in a model of cardiac damage induced by doxorubicin (Lu, Lu, Gao, Wang, & Wang, 2021;Zhai et al, 2020) or isoproterenol (Cheng, Zhao, Tse, Le, & Rong, 2015; Huang Khan et al, 2022;Pan et al, 2021), including MI. ALDH2 activation has been shown to enhance anti-oxidative capacity of cells, which is involved in scavenging harmful aldehydes such as MDA and 4-HNE, resulting in a decrease in cellular ROS generation (Islam et al, 2021;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…ALDH2, a mitochondrial protein enzyme that is highly expressed in the heart, is the key enzyme responsible for the detoxification of toxic aldehydes in the heart. Numerous studies have established that ALDH2 deficiency or dysregulation is frequently associated with a variety of oxidative stress‐induced diseases (He et al, 2021; Ji et al, 2021; Khan et al, 2022; Pan et al, 2021), including MI. ALDH2 activation has been shown to enhance anti‐oxidative capacity of cells, which is involved in scavenging harmful aldehydes such as MDA and 4‐HNE, resulting in a decrease in cellular ROS generation (Islam et al, 2021; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ALDH2 ( Figure 3(c) , spot #D20) is essential for the removal of toxic aldehydes that are by-products of lipid peroxidation in the RPE [ 52 ]. In a recent study, overexpression of ALDH2 restored retinal function by reducing apoptosis and enhancing chaperone activity in mice [ 53 ]. Glutamine synthetase is an enzyme that generates glutamine via the condensation of glutamate and ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…Ausra et al [ 87 ] showed that ALDH2 may play a protective role in human OA chondrocytes. Moreover, a recent study demonstrated that ALDH2 could alleviate MIA‑induced oxidative stress, inflammation and apoptosis in chondrocytes via inhibiting aquaporin 4 expression [ 88 ].…”
Section: Pathological Aspects Of Lipid Peroxidation In Oamentioning
confidence: 99%